Assessment of the effectiveness of head only and back-of-the-head electrical stunning of chickens. Issue 3 (3rd May 2016) - Gibson, T. J.; Taylor, A. H.; Gregory, N. G.
Abstract: The study assesses the effectiveness of reversible head-only and back-of-the-head electrical stunning of chickens using 130–950 mA per bird at 50 Hz AC. Three trials were conducted to compare both stunning systems: (a) behavioural assessment of return of consciousness, (b) insensibility to thermal pain, and (c) assessment of return of brain activity with visually evoked potentials (VEPs). Assessment of behaviour suggested that the period of unconsciousness following head-only electrical stunning was shorter in hens compared to broilers. Stunning across the back-of-the-head delayed the time to return of brainstem function compared to stunning with standard head-only electrodes. Additionally, back-of-the-head stunning produced a more prolonged period of electroanalgesia compared to head-only. Based on examination of return of brain function with VEPs in hens, back-of-the-head stunning produced a shorter-lasting stun than standard head-only. However, even for standard head-only, the stun was notably shorter than previously reported. In some birds, brain function had returned within 9 s after the end of stunning. The results suggest that some birds may recover consciousness prior to or during the neck cut. Based on these findings, back-of-the-head stunning and standard head-only stunning of hens should not be recommended without further development.